Peran Pers Dalam Menanggulangi Hoaks Pemilu - Nesya Desriany Mustapa; Nara Rafi Zulfikar; Muhammad Alif Athaariq (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to find out the role of the press in disseminating information about elections and policies related to press obligations in this election era. Journalism as the fourth pillar of democracy has a key role in educating the public and providing space for public participation in order to actively participate in maintaining democracy. During the election period, where political tensions and competition between parties reach their peak, the existence of journalistic ethics guidelines becomes even more crucial. The formulation of journalistic ethics guidelines policy in the Press Law is a strategic step to ensure that media coverage during elections remains quality, objective, and makes a positive contribution to the democratic process. The document analysis approach is a qualitative method used in the preparation of this article. In addition, in search of relevant data, we as researchers tried to do website scraping on one of the national news sites